PENGARUH PEMBELAJARAN BERBASIS GAMIFIKASI TERHADAP MOTIVASI BELAJAR MELALUI PEMAHAMAN KONSEP SISWA MPLB SMKN 16 JAKARTA - Tia Atika Maharani; Dewi Nurmalasari; Susan Febriantina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the effect of gamification-based learning on students' learning motivation through conceptual understanding among Office Management and Business Services (MPLB) students at SMKN 16 Jakarta. This research employed a quantitative approach using a survey method. The population consisted of Grade X and XI MPLB students at SMKN 16 Jakarta, with a sample of 105 respondents selected using proportionate stratified random sampling. Data were collected through questionnaires and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach with SmartPLS 4.0 software. The findings indicate that gamification-based learning has a positive and significant effect on learning motivation (β = 0.239; p < 0.001) and conceptual understanding (β = 0.688; p < 0.001). Furthermore, conceptual understanding has a positive and significant effect on learning motivation (β = 0.643; p < 0.001). The mediation analysis also reveals that conceptual understanding significantly mediates the relationship between gamification-based learning and learning motivation (T-statistics = 8.818; p < 0.001). These findings suggest that the implementation of gamification elements, such as points, badges, challenges, and feedback, not only enhances students' engagement in the learning process but also improves their conceptual understanding, which ultimately strengthens their learning motivation. This study implies that gamification-based learning can serve as an effective instructional strategy for improving the quality of teaching and learning outcomes in vocational education.